Endogenous GLP-1 in lateral septum contributes to stress-induced hypophagia - Terrill, Sarah J. (Physiol Behav, 2018)
Glucagon-like peptide 1 (GLP-1) neurons of the caudal brainstem project to many brain areas, including the lateral septum (LS), which has a known role in stress responses. Previously, we showed that endogenous GLP-1 in the LS plays a physiologic role in the control of feeding under non-stressed conditions, however, central GLP-1 is also involved in behavioral and endocrine responses to stress. Here, we asked whether LS GLP-1 receptors (GLP-1R) contribute to stress-induced hypophagia. Male rats were implanted with bilateral cannulas targeting the dorsal subregion of the LS (dLS). In a within-subjects design, shortly before the onset of the dark phase, rats received dLS injections of saline or the GLP-1R antagonist Exendin (9-39) (Ex9) prior to 30 min restraint stress. Food intake was measured continuously for the next 20 h. The stress-induced hypophagia observed within the first 30 minutes of dark was not influenced by Ex9 pretreatment, but Ex9 tended to blunt the effect of stress as early as 1 and 2 h into the dark phase. By 4–6 h, there were significant stress X drug interactions, and Ex9 pretreatment blocked the stress-induced suppression of feeding. These effects were mediated entirely through changes in average meal size; stress suppressed meal size while dLS Ex9 attenuated this effect. Using a similar design, we examined the role of dLS GLP-1R in the neuroendocrine response to acute restraint stress. As expected, stress potently increased serum corticosterone, but blockade of dLS GLP-1Rs did not affect this response. Together, these data show that endogenous GLP-1 action in the dLS plays a role in some but not all of the physiologic responses to acute stress.